Immunological correlates of behavioral problems in school-aged children living with HIV in Kayunga, Uganda. (25th June 2015) - Ruiseñor-Escudero, H.; Familiar, I.; Nakasujja, N.; Bangirana, P.; Opoka, R.; Giordani, B.; Boivin, M.
Abstract : Background: HIV can affect the neuropsychological function of children, including their behavior. We aim to identify immunological correlates of behavioral problems among children living with HIV in Uganda. Methods: Children participating in a parent randomized control trial in Kayunga, Uganda were assessed with the Behavior Rating Inventory of Executive Function (BRIEF) and the Child Behavior Checklist (CBCL). We constructed simple and multiple linear regression models to identify immunological correlates of behavioral problems. Results: A total of 144 children living with HIV (50% male) with a mean age of 8.9 years [Standard Deviation (s.d. ) = 1.9] were included in the analysis. Eighty-two children were on antiretroviral therapy. Mean CD4 cell count % was 35.1 cells/μl (s.d. = 15.0), mean CD4 cell activation 5.7% (s.d. = 5.1), mean CD8 cell activation was 17.5% (s.d. = 11.2) and 60 children (41.7%) had a viral load of <4000 copies/ml. In the adjusted models for the BRIEF, higher scores were associated with higher viral loads (aβ = 16.7 × 10 −6, 95% CI −5.00 × 10 −6 to 28.4 × 10 −6 ), specifically on the behavioral regulation index. Higher mean CD8 activation % was associated with higher scores on the Externalizing Problems and Total Problems scales of the CBCL (aβ = 0.17, 95% CI 0.04–0.31 and aβ = 0.15, 95% CI 0.00–0.28, respectively). Conclusions: Poorer behavioral outcomes were associated with higher viral loads while higher CD8 activation was associated with poorer emotional and behavioral outcomes. Complete immunological assessments for children living with HIV could include commonly used viral and immunological parameters to identify those at higher risk of having negative behavior outcomes and who would benefit the most from behavioral interventions.